Legal, Social, and Occupational Problems in Persons with Alcohol Use Disorder: An Exploratory Study - Malathesh, Barikar C (Indian J Psychol Med, 2020)
BACKGROUND: Very few studies have examined the extent and nature of legal, social, and occupational problems among persons who have SUDs. This study was aimed at studying the prevalence and patterns of the aforementioned problems among individuals with alcohol use disorders (AUDs) and their relationship with the quantity of alcohol consumed and other variables. METHODS: We conducted a cross-sectional study of adult patients with a diagnosis of AUDs admitted to the deaddiction unit of a tertiary care facility in India, using a semistructured questionnaire prepared for this study. RESULTS: The mean age (SD) of the 91 subjects (95.6% males) was 40.3 years (8.5). Majority of them (92.3%) had started alcohol consumption before the age of 25 years. Common problems reported were work absenteeism (83.5%), a major altercation with spouse (69.3%), assaulting someone while intoxicated (53.8%), and driving under the influence of alcohol (59.3%). Significant association was found between being unemployed and having a police complaint lodged against them (chi-square = 5.7, P = 0.01). Quantity of alcohol consumed per day was significantly more among those who had a history of work absenteeism (Z = 2.27, P = 0.01), major altercation with spouse (Z = 2.25, P = 0.02) and assaulted someone under intoxication (Z = 2.33, P = 0.02). CONCLUSION: The quantity of alcohol consumed is significantly more in those who had several legal, social, and occupational problems when compared to those who did not have, highlighting the need for routine assessment of the aforementioned problems among patients of AUDs. Treatment of AUDs should be multidisciplinary, with targeted interventions tailored to the aforementioned problems. Doing so will go a long way in reducing the harm to patients and the community at large.